2015
DOI: 10.1186/s13071-015-1266-7
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and evolutionary genetics of the three major Plasmodium vivax merozoite genes participating in reticulocyte invasion in southern Mexico

Abstract: BackgroundReported malaria cases in the Americas had been reduced to about one-half million by 2012. To advance towards elimination of this disease, it is necessary to gain insights into how the malaria parasite is evolving, including the emergence, spread and persistence of new haplotypes in affected regions. In here, the genetic diversity of the three major P. vivax merozoite genes was analyzed.MethodsFrom P. vivax-infected blood samples obtained in southern Mexico (SMX) during 2006–2007, nucleotide sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 83 publications
4
26
0
Order By: Relevance
“…These values are similar to those reported for a sample of 35 parasites from 2006–2007 [36], and above those calculated for parasites from Venezuela [33] or South Korea [31], both sites of low transmission [2]. Other geographic sites with high transmission had greater genetic diversity (0.0073–0.0101), including Iran [32], India [29, 49], Sri Lanka [28], PNG [22] and Thailand [30] (Additional file 3: Table S2).…”
Section: Resultssupporting
confidence: 90%
“…These values are similar to those reported for a sample of 35 parasites from 2006–2007 [36], and above those calculated for parasites from Venezuela [33] or South Korea [31], both sites of low transmission [2]. Other geographic sites with high transmission had greater genetic diversity (0.0073–0.0101), including Iran [32], India [29, 49], Sri Lanka [28], PNG [22] and Thailand [30] (Additional file 3: Table S2).…”
Section: Resultssupporting
confidence: 90%
“…Comparison of the most common amino acid variants observed globally in PvDBPII revealed that Sudan isolates showed a comparatively similar pattern of minor allele frequency to Mexico isolates, but differed from other countries isolates (Papua New Guinea, Colombia, Brazil, Iran, India, Sri Lanka) (Table 1 ). Although Mexican isolates showed similar amino acid changes compared to Sudan isolates, 2 variants found in the Sudan isolates (D497N and T513K) were not identified in Mexican isolates [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although Mexican isolates showed similar amino acid changes compared to Sudan isolates, 2 variants found in the Sudan isolates (D497N and T513K) were not identified in Mexican isolates [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the greatest challenges in the development of effective vaccines which are capable of generating an efficient antigen-specific immune response is the high level of polymorphic sequences. Genetic variability has been assessed in many important P. vivax vaccine candidates, such as CSP [ 30 , 31 ], DBP [ 32 , 33 ], MSP-1 [ 33 , 34 ], MSP-3 alpha [ 35 ], MSP-4 [ 36 ], MSP-5 [ 37 ], MSP-7 [ 38 ], MSP-9 [ 39 ], RAP-1 [ 40 ], RAP-2 [ 40 ], Pvs48/45 [ 41 ], PvGCS1 [ 42 ], TRAP [ 43 ], and PvCelTOS [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins involved in the MJ complex formation have also been characterized. PvAMA1 has been analysed and characterized in multiple studies on field isolates from different endemic area [ 29 , 33 , 45 , 46 ]. PvAMA1 is a highly polymorphic antigen [ 29 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%